Factors Affecting to Saving of Enterprise Employees in Oudomxay Province - PANYASACK, Vilasack; SOMSAMONE, Vilayphone; SYPHADA, Vatthanaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The study of the factors affecting the saving of state enterprise employees in Oudomxay province aims to study the behavior of saving and factors affecting the saving of state enterprise employees within Oudomxay province. Which used a questionnaire to collect data from a sample group of 183 people using basic statistics and analyzed it with the least square regression analysis model (Ordinary Least Square). The result of the study found that most of the reasons why state enterprise employees decide to save money are for security in life, accounting for 79.78%, with the people who influence the decision to save money the most being themselves, and accounting for 49.18%, of which 57.38% do not specify the exact amount of saving money. The method of saving money is deducted from the salary account, accounting for 45.36%. The average amount of money that can be saved per month is between 500,001 - 2,000,000 kip. Covering 56.28%, with most of the average frequency of saving money per month being 1 time covering 76.50%, the selected period of ablution is indefinite, covering 49.46%. The form of withdrawal is depositing at banks or financial institutions, covering 94.54%, and the goal of withdrawing money is mainly to spend in emergencies, covering 65.57%, with 100% choosing to continue withdrawing money, and if they continue to withdraw, they will withdraw as before, covering 55.19%. The factors that affect retirement in the same direction include: interest rate, retirement preparation, and monthly income, number of branches of the institution, interesting promotion activities, and expectation of results. The correlation factors in the opposite direction include: daily life expenses, travel transaction fees, and health expenses, with a statistical significance level of 99%, 95%, and 90%, respectively.